Effects of strength training associated with whole-body vibration training on running economy and vertical stiffness - Roschel, H.; Barroso, R.; Tricoli, V.; Batista, M. A. B.; Acquesta, F. M.; Serrão, J. C.; Ugrinowitsch, C. (The Journal of Strength and Conditioning Research, 2015)
Running economy (RE) is defined as the energy cost to maintain a submaximal running velocity and seems to be affected by individual's neuromuscular characteristics, such as stiffness level. Both resistance training (RT) and whole-body vibration training added to RT (WBV + RT) have been shown to influence those characteristics. Thus, it is conceivable that RT and WBV + RT could also affect RE. The objective of this study was to investigate if a 6-week training period of RT and WBV + RT influences RE and vertical stiffness (VS). Fifteen recreational runners were divided into RT or WBV + RT groups. Running economy, VS, and lower-limb maximum dynamic strength (1 repetition maximum [1RM] half-squat) were assessed before and after the 6-week training period. There was a main time effect for 1RM, but no other statistically significant difference was observed. Neither conventional RT nor RT performed on a WBV platform improved VS and RE in recreational long distance runners. It is possible that movement velocity was rather low, and utilization of stretch-shortening cycle might have been compromised, impairing any expected improvement in RE.